2008
DOI: 10.1002/chem.200701537
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Syntheses of Copper Cubanes, Double‐Stranded Copper/Palladium Helicates, and a (Dilithium)–Dinickel Coronate from Enantiomerically Pure Bis‐1,3‐diketones—Solid‐State Self‐Organization Towards Wirelike Copper/Palladium Strands

Abstract: Enantiomerically pure, vicinal diols 1 afforded in a two-step synthesis (etherification and subsequent Claisen condensation) chiral bis-1,3-diketones H(2)L((S,S)) (3 a-c) with different substitution patterns. Reaction of these C(2)-symmetric ligands with various transition-metal acetates in the presence of alkali ions generated distinct polynuclear aggregates 4-8 by diastereoselective self-assembly. Starting from copper(II) acetate monohydrate and depending on the ratio of transition-metal ion to alkali ion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 142 publications
0
7
0
3
Order By: Relevance
“…The CD spectrum of 28 exhibits two negative and one positive Cotton effect, while ent-28 shows Cotton effects of the opposite sign at the same wavelengths ( Figure 17). [21] 3.6. Threading of Copper(II) and Palladium(II) Ions…”
Section: Meandering Meso-polymer Stringsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CD spectrum of 28 exhibits two negative and one positive Cotton effect, while ent-28 shows Cotton effects of the opposite sign at the same wavelengths ( Figure 17). [21] 3.6. Threading of Copper(II) and Palladium(II) Ions…”
Section: Meandering Meso-polymer Stringsmentioning
confidence: 99%
“…Analogously, (P)-[Pd 2 (L (S,S) ) 2 ] (30) could be obtained from palladium(II) acetate in the presence of one equivalent of pyridine (Scheme 12). [21] Interestingly, the molecules 29 and 30 are packed in the crystal in parallel, leading to copper and palladium metal strings with short intra-and intermolecular metal-metal separations ( Figure 18). [21] Scheme 10.…”
Section: Meandering Meso-polymer Stringsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both hydrophilic and hydrophobic regions, respectively, were present in the interior and exterior part of 190 and the disordered water or ethanol solvent of crystallization were located inside the cluster (Fig. 85) Bis(␤-diketone) derivatives can be utilized as chelates for the construction of discrete and extended metal-organic architectures [291][292][293][294][295]. Two hexanuclear metallacycles [Cu 6 L150 3 Py 8 ]·6.25Py (191a) and [Cu 3 Ni 3 L150 3 Py 9 ]·3.25Py (191b) (L150 = 1,4-aryl linked bis(␤,␦-triketone)) were self-assembled by the reaction of L150 with Cu II salt or a combination of Ni II and Cu II salts followed by recrystallization of the product from pyridine (Scheme 71) [296].…”
Section: Multinuclear Metallacyclesmentioning
confidence: 99%
“…3 We, and others, have found that ligands incorporating more than one β-diketone motif react with selected metal ions to yield an array of metallo-supramolecular architectures with the products in many instances exhibiting a significant degree of predictability. 1,3,10 Structures generated with these ligands include helicates, [11][12][13][14] tetrahedra, 15,16 boxes, 17 capsules 18 and an unprecedented universal 3-ravel; 14 for example, the well defined coordination vectors of ligands L 1-3 produce neutral planar metallocyclic species of type [M 2 (L 1 ) 2 ] (1) 11,13,[19][20][21] [M 3 (L 2 ) 3 ] (2) 16,22 and the larger [M 3 (L 3 ) 3 ] (3) 23,24 upon reaction with selected divalent transition metals.…”
Section: Introductionmentioning
confidence: 99%